Risk factors for intrahepatic and extrahepatic cholangiocarcinoma in the United States: A population-based study in SEER-Medicare - Petrick, Jessica L.; Yang, Baiyu; Altekruse, Sean F.; Van Dyke, Alison L.; Koshiol, Jill; Graubard, Barry I.; McGlynn, Katherine A. (PloS one, 2017)
Intrahepatic (ICC) and extrahepatic (ECC) cholangiocarcinomas are rare tumors that arise from the epithelial cells of the bile ducts, and the etiology of both cancer types is poorly understood. Thus, we utilized the Surveillance, Epidemiology, and End Results (SEER)-Medicare resource to examine risk factors and novel preexisting medical conditions that may be associated with these cancer types. Between 2000 and 2011, 2,092 ICC and 2,981 ECC cases and 323,615 controls were identified using the SEER-Medicare database. Logistic regression was used to calculate adjusted odds ratios (OR) and 95% confidence intervals (CI). Non-alcoholic fatty liver disease was associated with approximately 3-fold increased risks of ICC (OR = 3.52, 95% CI: 2.87-4.32) and ECC (OR = 2.93, 95% CI: 2.42-3.55). Other metabolic conditions, including obesity and type 2 diabetes, were also associated with increased risks of both cancer types. Smoking was associated with a 46% and 77% increased ICC and ECC risk, respectively. Several autoimmune/inflammatory conditions, including type 1 diabetes and gout, were associated with increased risks of ICC/ECC. As anticipated, viral hepatitis, alcohol-related disorders, and bile duct conditions were associated with both cancer types. However, thyrotoxicosis and hemochromatosis were associated with an increased risk of ICC but not ECC, but did not remain significantly associated after Bonferroni correction. In this study, risk factors for ICC and ECC were similar, with the exceptions of thyrotoxicosis and hemochromatosis. Notably, metabolic conditions were associated with both cancer types. As metabolic conditions are increasing in prevalence, these could be increasingly important risk factors for both types of cholangiocarcinoma.